2015
DOI: 10.1177/0733464815617284
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Online Theory-Based Bone Health Program for Older Adults

Abstract: An estimated 10 million Americans age 50 and older have osteoporosis, and many experience associated fractures. Although several interventions have been shown to be effective in preventing osteoporosis, their impact on bone health among older adults was limited. The aim of this study was, therefore, to examine the effects of a theory-based online bone health program (Bone Power program) for a large number of older adults. The 8-week program included learning modules, discussion boards, and other resources. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…The most frequently observed form of bias was selection bias (asking for volunteers for a research study involving technology will result in volunteers who already gravitate toward technology), which occurred in 7 out of 57 (13%) articles analyzed [ 15 , 26 , 30 - 32 , 37 , 39 ]. There were six instances of convenience samples from a local population [ 34 , 49 - 52 , 64 ]. Both examples of bias limit the external validity of the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently observed form of bias was selection bias (asking for volunteers for a research study involving technology will result in volunteers who already gravitate toward technology), which occurred in 7 out of 57 (13%) articles analyzed [ 15 , 26 , 30 - 32 , 37 , 39 ]. There were six instances of convenience samples from a local population [ 34 , 49 - 52 , 64 ]. Both examples of bias limit the external validity of the results.…”
Section: Resultsmentioning
confidence: 99%
“…The most common theme for medical outcomes associated with telehealth interventions was decrease in psychological distress (decrease in anxiety symptoms, decrease in depressive symptoms, decrease in embitterment, decrease in grief, decrease in worry, decrease in loneliness, increase in emotional support, and increase in mood), with 21 of 118 (18%) occurrences [ 32 , 42 , 46 , 51 , 60 , 68 , 70 , 71 , 76 ]. The theme associated with quality of life factors was listed as an increase in autonomy (increase in locus of control, increase in autonomy, increase in responsibility, increase in motivation to self-manage, and increase in independence), with 18 of 118 (15%) occurrences [ 29 , 34 , 35 , 46 , 48 , 52 - 54 , 56 , 62 , 67 , 75 , 76 ]. One theme was associated with an increase in cognitive ability (increase in skill ability, increase in sensory organization, increase in memory, increase in cognitive activity, and increase in reasoning), with 11 of 118 (9%) occurrences [ 19 , 20 , 23 , 32 , 41 , 42 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed that the common reasons for older people to avoid performing physical activities are inconvenience and a lack of access to physical activity programmes [68]. This review found that walking is the most commonly targeted physical activity for older people since there are no problems involved with gaining access to programmes, because it is an activity that can be practised anywhere.…”
Section: Discussionmentioning
confidence: 97%
“…Because an estimated 59% of adults aged 65 and older use the internet [69] , online interventions may reach a substantial proportion of the geriatric population at risk for future fracture, as evidenced by our findings. In one study, older adult exposure to an 8-week theory-based program entitled Bone Power that included learning modules, discussion boards, and other resources resulted in greater improvement in osteoporosis knowledge, self-efficacy/outcome expectations for calcium intake and exercise behaviors compared to the group of adults who were not exposed [70] . In our past experience, a direct-to-patient, internet-based educational video intervention produced a trend toward greater use of osteoporosis medication among patients taking chronic glucocorticoids when the patients self-initiated an educational video on osteoporosis prevention [71] .…”
Section: Discussionmentioning
confidence: 99%